Exploring the Impact of Transformational Leadership on Employee Career Development in the Financial Services Sector - Adrian K Tarigan; Anju Bherna D Nainggolan; Diana Florenta Butarbutar; Margono Margono; Markus Doddy Simanjuntak (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Transformational leadership plays a vital role in enhancing employee career development by fostering motivation and professional growth in organizations. This study aims to examine the influence of transformational leadership on employee career development within a state-owned financial institution in Indonesia. Data were collected from 30 employees using a questionnaire with a five-point Likert scale, designed to measure perceptions of leadership and career progression, and analyzed through statistical methods to test the relationship between variables. The findings reveal that transformational leadership, characterized by inspirational motivation, intellectual stimulation, idealized influence, and individual consideration, significantly enhances employees’ skills, career advancement, and motivation. Leaders who provide personalized support and a clear vision create a supportive environment that aligns individual aspirations with organizational goals. In conclusion, transformational leadership is a key driver of career development, offering practical insights for improving leadership practices in financial institutions. Organizations should invest in training programs to cultivate transformational leadership skills, ensuring sustained employee growth and organizational success. This study highlights the importance of effective leadership in addressing career development challenges and fostering a motivated workforce.